(untitled) (Clinics, 2012)
OBJECTIVE: Chagas' disease has spread throughout Latin America because of the high rate of migration among these countries. Approximately 30% of Chagas' patients will develop cardiomyopathy, and 10% of these will develop severe cardiac damage leading to heart failure. Beta-blockade improves symptoms and survival in heart failure patients; however, its efficacy has not been well established in Chagas' disease. We evaluated the role of carvedilol in cardiac remodeling and mortality in a Chagas' cardiomyopathy animal model. METHODS: We studied Trypanosoma cruzi infection in 55 Syrian hamsters that were divided into three groups: control (15), infected (20), and infected + carvedilol (20). Animals underwent echocardiography, electrocardiography, and morphometry for collagen evaluation in ventricles stained with picrosirius red. RESULTS: The left ventricular diastolic diameter did not change between groups, although it was slightly larger in infected groups, as was left ventricular systolic diameter. Fractional shortening also did not change between groups, although it was slightly lower in infected groups. Collagen accumulation in the interstitial myocardial space was significantly higher in infected groups and was not attenuated by carvedilol. The same response was observed in the perivascular space. The survival curve showed significantly better survival in the control group compared with the infected groups; but no benefit of carvedilol was observed during the study. However, in the acute phase (up to 100 days of infection), carvedilol did reduce mortality. CONCLUSION: Carvedilol did not attenuate cardiac remodeling or mortality in this model of Chagas' cardiomyopathy. The treatment did improve survival in the acute phase of the disease.